Women are Key to Union Renewal: Lessons from the Canadian Labour Movement - Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (Paths to Union Renewal: Canadian Experiences, 2006)
[E]xamines the ways in which union organizing gender-baised and highlights possible union strategies to overcome the bias and improve organizing success. ...The paper draws on the survey of union organizers in Ontario and British Columbia conducted by the authors in 2000 and 2001. –Editors' introduction
https://utorontopress.com/9781551930589/paths-to-union-renewal/
Keywords: Labor Unions; Labor movement; Organizational change